2022
DOI: 10.1021/acsomega.2c00141
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Various Substituted (Thio)Ureas, Semicarbazides, Thiosemicarbazides, Thiazolidones, and Oxadiazole Derived from [2.2]Paracyclophane

Abstract: The strategies of the syntheses of various (thio)ureas, semicarbazides, thiosemicarbazides, thiazolidones, and oxadiazole derived from the [2.2]paracyclophane molecule are achieved starting with 4-(2.2]paracyclophanyl)isocyanate. The structures of the obtained products were elucidated by NMR, mass spectrometry, and infrared (IR) spectroscopy in addition to high-resolution mass spectrometry (HRMS). X-ray structure analysis was also used to prove the assigned structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…We recently reacted thioureas bearing a [2.2]paracyclophane moiety with diethyl acetylene-dicarboxylate ( 4a ) to form thiazolidinones ( Alshammari et al, 2022 ). An X-ray crystal structure showed the C=N and C=C double bonds to both have ( Z ) stereochemistry ( Figure 5 ); in the current series 5a-l, we assign the C=N and C=C bonds as both ( Z ) by analogy with our earlier work.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reacted thioureas bearing a [2.2]paracyclophane moiety with diethyl acetylene-dicarboxylate ( 4a ) to form thiazolidinones ( Alshammari et al, 2022 ). An X-ray crystal structure showed the C=N and C=C double bonds to both have ( Z ) stereochemistry ( Figure 5 ); in the current series 5a-l, we assign the C=N and C=C bonds as both ( Z ) by analogy with our earlier work.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Aly et al reported that 2-(4′-[2.2]paracyclophanyl-4 H - N -substituted-hydrazine-carbothioamides 7a – f were prepared in 80–88% yields by refluxing compound 6 with the isothiocyanates in EtOH for 6–8 h ( Scheme 3 ) [ 52 ].…”
Section: Synthesis Of Thiosemicarbazide Derivativesmentioning
confidence: 99%